PENGARUH PEMBERIAN PUPUK HAYATI DAN MIKORIZA TERHADAP INTENSITAS SERANGAN PENYAKIT LAYU BAKTERI (Ralstonia solanacearum), PERTUMBUHAN, DAN HASIL TANAMAN TOMAT - Fatimatul Aulia; Hilda Susanti; Edwin Noor Fikri (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2016)
The research about the effect of applications biofertilizer and mycorhiza to intensity attack of bacterial wilt disease, growth, and yield of tomato was conducted in trial garden of Agriculture Faculty Lambung Mangkurat University from November 2015 until February 2016. The experiment was arranged in a completely randomized design with one factor, four treatments (no treatment (control), biofertilizer, mycorhiza, and biofertilizer + mycorhiza), and five replications. The results of experiment were compared to control showed that the applications of biofertilizer + mycorhiza could reduce intensity attack of bacterial wilt disease by 29.20%, flowering time was 10 days faster , and fresh weight of fruit was 122 g heavier. The increasing of plant height and stem number did not affected by all treatments.